The Effectiveness of Moringa Leaf Simplicia on the Adequacy of Breast Milk in Babies Less Than 6 Months Old In Terms Of the Baby's Weight at the Health Center - Sunarsih, Ni Komang; Mastiningsih, Putu; Putu Novi Ekajayanti, Pande (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2022)
Breast milk (breast milk) is the best food for babies. The benefits of breastfeeding can be felt by babies, mothers and families, but data shows that breastfeeding for toddlers in Indonesia is still very low. Factors that can influence mothers not to give breast milk to their babies include insufficient milk production. A sign of sufficient milk in infants is their weight gain of more than 10% in the first week. The baby's weight will increase by 200-2500 grams per week. The smoothness of breast milk production is influenced by many factors, namely the nutritional status of the mother, mother's nutrition can be met with alternative Moringa (Moringa oleifera) plants, because they contain phytosterol compounds which function to increase and facilitate milk production. In babies less than 6 months in terms of baby's weight in the Posyandu in the working area of the Tembuku I Health Center. This study uses the Quasi Experimental research method with the posttest only control design where in this research design there will be an experimental group and a control group. The sample in this study was 30 mothers breastfeeding babies less than 6 months, divided into 2 groups, namely 15 people in the experimental group and 15 people in the control group. Data were analyzed using Independent t-test. Results Analysis using statistical tests in this study was carried out using the independent-T Test test, the results obtained were that the p value was 0.025 < α 0.05. Thus the administration of Moringa leaf simplicia to breastfeeding mothers affects the baby's weight in the posyandu working area of the Tembuku I Health Center. Keywords : Baby, Breast Milk, Moringa leaves, Simplicia